Middle-distance front crawl determinants when using a wetsuit - Gay, A.; Ruiz-Navarro, J. J.; Cuenca-Fernández, F.; López-Belmonte, O.; Fernandes, R. J.; Arellano, R. (International Journal of Sports Medicine, 2023)
Our aim was to establish the determinants explaining the wetsuit advantages in middle-distance swimming efforts. Thirty-one triathletes and open water swimmers performed two 400 m front crawl bouts in a 25 m swimming pool with swim and wetsuits (with 48 h rest in-between). Anthropometric, kinematic and physiological variables were measured and Pearson correlation coefficients and stepwise linear regression analysis were used to determine their relationships. Associations observed in the 400 m front crawl included time improved using wetsuit with swimmers age (r=0.38; p=0.017), cross-sectional area (r=0.33; p=0.034), wetsuit upper limbs thickness (r=-0.49; p=0.010), deltaInternational Swimming Federation Points (r=-0.39;p=0.016), deltastroke rate (SR, r=0.48; p=0.003), deltastroke length (SL, r=-0.39; p=0.015), deltapropelling efficiency (r=-0.37; p=0.019) and deltablood lactate concentrations (r=0.30; p=0.048) in the total sample. In females, associations were found between the time improved and wetsuit upper and lower limbs thickness (both r=-0.78; p=0.011), and in males associations were found between time improved and age (r=0.43; p=0.030), deltaSR (r=0.56; p=0.005) and deltaSL (r=-0.44; p=0.026). Furthermore, 48% of the 400 m front crawl time improved was explained by wetsuit upper limbs thickness and SR changes (total sample), 62% explained by the wetsuit lower limbs thickness (females) and 48% of this enhancement was related to age and SR changes (males). Therefore, faster upper and lower limbs actions and wetsuit upper and lower limbs thickness are beneficial for 400 m front crawl performance improvement.